THE INFLUENCE OF BUDGET PARTICIPATION, ORGANIZATIONAL CULTURE, ORGANIZATIONAL COMMITMENT AND ENVIRONMENTAL UNCERTAINTY ON BUDGET SLACK IN LANGKAT REGENCY GOVERNMENT - Asmara, Rizqy Winny; Fachrudin, Khaira Amalia; Irawati, Nisrul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
The research aims to examine the influence of budget participation, organizational culture, organizational commitment, and environmental uncertainty on budget slack in the Langkat Regency Government. The type of data used in this research is primary data using a questionnaire. The population in this study were all employees of the Langkat Regency Government. The sample in the research consisted of 89 respondents who were involved in budget preparation. The method used to determine the sample is the purposive sampling technique. The data analysis method used in this research is the multiple linear regression method. The research results show that environmental uncertainty has a significant positive effect on the budget slack. Meanwhile, budget participation, organizational culture, organizational commitment, and environmental uncertainty do not affect the budget slack in the Langkat Regency Government.